Preparing a nutrient solution for hidroponic cultures by using waste mash from the Vitis vinífera L. grape - Ramón Ferrer, José; Sánchez Jaimes, Edgar (Rev. Téc. Fac. Ing. Univ. Zulia, 2011)
In this project, waste mash from grapes was used in the preparation of compost which was then anaIyzed as a nutrient medium (in the form of a nutrient solution) to replace the traditional mineral-based solutions used in hidroponics. The compost and the aqueous solutions prepared there from were studied under different experimental conditions (types of stirring: orbital, vibrational and magnetic; stirring times in hours: 1, 2, 4, 6, 8, 10, 12 and 14: types of water: destilled and direct from the tap; type of filtering. and so on). They were characterized, by volumetric. colorimetric, turbidimetric and instrumental (AAE) chemical analysis, then evaluated and compared with nutriente solutions traditionally used in hidroponics. The solutions thus evaluated contained high concentration levels of nutrients, approximating those reported in the literature for traditional nutrient solutions. In a comparative study between one of the traditional solutions and one of those under study, the cultures obtained displayed similar physcal-chemical, organoleptic and nutritional characteristics, there being a prominent average of 24.40% raw protein in forage cultures from the latter solution.